Ponesimod, a selective sphingosine 1-phosphate (S1P1) receptor modulator for autoimmune diseases: review of clinical pharmacokinetics and drug disposition - Dash, Ranjeet Prasad; Rais, Rana; Srinivas, Nuggehally R. (Xenobiotica, 2018)
1. Ponesimod, a selective sphingosine 1-phosphate (S1P 1 ) receptor modulator, is undergoing clinical development for the treatment of autoimmune diseases (multiple sclerosis/psoriasis). 2. Published literature data describing pharmacokinetic disposition of ponesimod were collected, reviewed and tabulated. 3. Across various clinical phase-I studies, ponesimod displayed consistent pharmacokinetics - relatively faster absorption peak time (approximately 2.5 h), elimination half-life of approximately 30 h and modest accumulation (2- to 2.6-fold). Ponesimod was extensively metabolized and two major metabolites were ACT-204426 and ACT-338375. 4. Extensive population pharmacokinetic-pharmacodynamic modeling has confirmed the therapeutic dose(s) for ponesimod to achieve the balance between safety (primarily heart rate) and efficacy using the maximum inhibition of the total lymphocytes as the pharmacodynamic marker. 5. None of the covariates (ethnicity, body weight, sex, diseased state including multiple sclerosis and psoriasis, food intake, formulation, etc.) examined in population pharmacokinetic model influenced the pharmacokinetics of ponesimod from a clinical relevance perspective. However, hepatic impairment (moderate/severe but not mild), profoundly influenced its disposition; and therefore, would necessitate dosage adjustment of ponesimod in clinical therapy. 6. Ponesimod has a favorable safety profile and pharmacokinetics, which will allow maximizing its ability to inhibit circulating lymphocytes in a given dosing regimen for treating autoimmune diseases.